Understanding the use of antibiotics and antibiotic resistance among Science stream and non-Science stream undergraduate students in a Malaysian university - Foo, Yik Lin; Subramaniam, Geetha; Sivasamugham, Lalita Ambigai; Hock, Ong Ghim; Agarwal, Anshoo (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: It is globally recognized that antibiotic resistance (ABR) has posed an enormous threat to society. Focusing on this issue, this study was carried out to assess the knowledge and attitude of science and non-science students in a tertiary institution in Malaysia towards antibiotics and antibiotic resistance. Methodology: A cross-sectional study was conducted from January to March 2020 among Science and non-science undergraduates. A random sample of 284 students from Biotechnology, Engineering, Business, and Mass Communication courses, were recruited into the study. An arbitrary scoring system was implemented for the assessment of the knowledge and attitude level of students based on the answer provided. The data was analyzed using Statistical Package for the Social Science (SPSS) version 26.0 Results: In this study, science students have significantly higher knowledge (52.8%, n=75) and attitude level (76.1%, n=108) than non-science students (32.4%, n=46) and (61.3%, n=87) respectively. Although 78% of the students, in general, acknowledged that antibiotics needed to be completed in time, there was still a lack of knowledge regarding ABR among the non-science students. Conclusion: An individual’s knowledge of antibiotic use is significant because personal decisions are made based on their knowledge and attitude. A higher knowledge level indicates a more positive attitude on antibiotic use and ABR. Hence, subsequent antibiotic awareness campaigns should be restructured to involve more non-science students to enhance their knowledge and correct the misconceptions of current students. Key Words: Antibiotics, antibiotic resistance, Science and non-Science students, Malaysia